8 - Imperfect Journey, Imperfect Cinema “A fast, ‘zinging’ shot scares the baboon!” - Belachew, Tekletsadik (Africa Development, 2017)
This article focusses on key themes in Haile Gerima’s Imperfect Journey, which, despite being one of the most important African documentaries, is often neglected by film critics and historians.1 Abba Gerima, the traditional playwright, dramatist, historian, and epic-poet, is discussed through selectively translated passages from two historical masterpieces that he originally wrote in Amharic and English translations. Abba Gerima’s and Haile Gerima’s historical and artistic texts are critically examined across history, aesthetics and the three mega themes of Imperfect Journey in order to understand how Abba Gerima’s vision is carried forward in the cinematic works of Haile Gerima.